2022
DOI: 10.1021/acsaem.2c02336
|View full text |Cite
|
Sign up to set email alerts
|

Deep Eutectic Solvent-Assisted Microwave Synthesis of Thermoelectric AgBiS2 and Cu3BiS3

Abstract: AgBiS2 and Cu3BiS3 were synthesized via a microwave-assisted solution route using a deep eutectic solvent (DES). The DES of choice consists of choline chloride and thiourea, with thiourea acting as a sulfur source. The DES synthesis route provides a fast, environmentally friendly, and low-temperature alternative to high-temperature (HT) synthesis. We compared DES synthesis to the synthesis from an aqueous solution and determined that the DES is preferred for the synthesis of Cu3BiS3, while deionized water is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 62 publications
7
1
1
Order By: Relevance
“…Here, the estimated value of bandgap is around 0.98 eV by assuming direct bandgap via plotting (αhν) 2 vs. (hν), as shown in Figure 7b. This result is in a good agreement with the reported values of AgBiS 2 grown via other methods [6,23]. While the AgBiS 2 powders provide a bandgap of 0.92 eV via the indirect bandgap Tauc plot, their linear fitting relationship is worse than that of the direct bandgap.…”
Section: Uv-vis Spectroscopy and Band Gap Characterizationssupporting
confidence: 91%
See 1 more Smart Citation
“…Here, the estimated value of bandgap is around 0.98 eV by assuming direct bandgap via plotting (αhν) 2 vs. (hν), as shown in Figure 7b. This result is in a good agreement with the reported values of AgBiS 2 grown via other methods [6,23]. While the AgBiS 2 powders provide a bandgap of 0.92 eV via the indirect bandgap Tauc plot, their linear fitting relationship is worse than that of the direct bandgap.…”
Section: Uv-vis Spectroscopy and Band Gap Characterizationssupporting
confidence: 91%
“…As shown in Figure 6, the black thermogravimetric (TG) curve represents the weight of the powders, the derivative thermogravimetric (DTG) curve represents the rate of weight change of the powders, and the blue differential thermal analysis (DTA) curve corresponds to the heat absorption and exothermic change of the powder sample as the temperature rises. It can be seen from the figure that when the temperature rises from room temperature to 700 • C, the weight loss of the powder sample does not exceed 5%; thus, it can be considered that AgBiS 2 has thermal stability below 700 • C. These results are comparable to previously reported values [23]. The observed weight gain or loss, as well as the absorptive or exothermic processes of the system observed in the curves, occur due to the small number of heterogeneous phases in the powder beyond the accuracy of XRD testing, including the desorption of adsorbed water, the heat absorption process of impurity phase oxidation, and the heat release process of decomposition.…”
Section: Structural Characteristicssupporting
confidence: 88%
“…The ρ(T) curve follows a nondegenerate semiconducting behavior with values decreasing from 130 Ω cm at 300 K to 0.36 Ω cm at 563 K. In the previous studies on Cu 3 BiS 3 , Wei et al reported a comparable value of 140 Ω cm at RT, while Adeyemi et al measured an electrical resistivity value of 17.2 Ω cm at 318 K, i.e., one order of magnitude lower than our value. 29,30 This is mainly explained by the larger grain sizes (1 order of magnitude larger) in the compounds synthesized by Adeyemi et al The high electrical resistivity in our sample is consistent with its high Seebeck coefficient S of 800 μV K −1 at RT (Figure S8b) and relatively low hole concentration of 1.7 × 10 16 cm −3 . Those values attest to the relatively high purity and stoichiometry of our sample thanks to the synthesis approach which combines mechanical-alloying followed by SPS, preventing heavy sulfur loss and stoichiometric deviation.…”
Section: ■ Introductionsupporting
confidence: 85%
“…The pristine phase Cu 3 BiS 3 has an extremely low lattice thermal conductivity (κ ≈ κ L due to the negligible electronic contribution) of 0.43 W m –1 K –1 at 300 K, which decreases as the temperature increases to reach 0.32 W m –1 K –1 at 563 K (Figure a). These values are slightly higher than those reported by Jia et al (0.32 W m –1 K –1 at 300 K), Adeyemi et al (0.29 W m –1 K –1 at 313 K), and Wei et al (0.17 W m –1 K –1 at 300 K). These differences could be the result of additional impurity phases and/or lower bulk sample density in these prior studies.…”
Section: Resultscontrasting
confidence: 59%
See 1 more Smart Citation